Factors That Affect Employee Effectiveness and Efficiency at PT. XYZ - Fahmi Hidayat (Enrichment : Journal of Management, 2019)
To enforce discipline is not enough just with threats, but it needs to be balanced, namely a sufficient level of welfare. Even so, actually discipline is not only determined by factors of well-being, but there are still many other factors, also need continuous habits. Based on preliminary research conducted at PT. Xyz, then the problem faced can be formulated as follows "what factors affect the effectiveness and efficiency of employee work at PT. Xyz", while the hypothesis of the problem is as follows: "factors that affect the effectiveness and efficiency of employee work are discipline". Discipline is an absolute requirement for employees of PT. Bandar Sumatra Indonesia..